The long run share price performance of Malaysian firms issuing equity private placements. (Prestasi jangka panjang syarikat-syarikat Malaysia yang menerbitkan tawaran persendirian ekuiti). - Norhafiza Nordin; Kamarun Nisham Taufil Mohd. (Penerbit Universiti Kebangsaan Malaysia, 2011)
The result of this study reveals an evidence of long run underperformance of equity private placements in Malaysia using market index as a benchmark. When the firms are matched to firms with similar size and market-to-book, they neither over-perform nor underperform the matching firms over the three-year period under the equal-weighting scheme. However, a considerable difference exists between the CARs and BHARs under the value-weighting scheme. Unlike previous studies that find small firms underperform more than large firms, results of this study show the opposite. We find that large firms show greater degree of underperformance than small firms. The result definitely does not conform to the widely acceptable idea that smaller firms are more likely to issue equity when they are overvalued due to higher degree of information asymmetry. Further results indicate that the underperformance is driven by the outlier in the sample. When it is excluded from the sample, no significant result is detected for the two-year period. Nevertheless, it is interesting to note that for both CAR and BHAR, the underperformance under equal-weighted scheme is worse when the returns are benchmarked against market index but in sharp contrast, the underperformance under value-weighted scheme is worse when the returns are benchmarked against matching firms.